NR4A1 inhibits the epithelial–mesenchymal transition of hepatic stellate cells: Involvement of TGF-β–Smad2/3/4–ZEB signaling - Huang Qian; Xu Jingying; Ge Yanyan; Shi Yue; Wang Fei; Zhu Mingli (Open Life Sciences, 2022)
This study aimed to examine whether nuclear receptor 4a1 (NR4A1) is involved in inhibiting hepatic stellate cell (HSC) activation and liver fibrosis through the epithelial–mesenchymal transition (EMT). HSC-T6 cells were divided into the control group, the acetaldehyde (200 μM, an EMT activator) group, and the NR4A1 activation group (Cytosporone B; 1 μM). The expression levels of the epithelial marker E-cadherin, the mesenchymal markers fibronectin (FN), vimentin, smooth muscle alpha-actin (α-SMA), and fibroblast-specific protein 1 (FSP-1), and the components of the transforming growth factor (TGF)-β pathway were detected by real-time polymerase chain reaction and western blotting. Compared with the control group, E-cadherin in the acetaldehyde group was downregulated, whereas FN, FSP-1, vimentin, α-SMA, and COL1A1/COL1A2 were upregulated (P < 0.05). Compared with the acetaldehyde group, NR4A1 agonist upregulated E-cadherin and downregulated FN, FSP-1, vimentin, α-SMA, and COL1A1/COL1A2 (P < 0.05). After acetaldehyde stimulation, TGF-β, Smad2/3/4, and zinc finger E-box-binding homeobox (ZEB) were upregulated, while Smad7 mRNA levels were downregulated (all P < 0.05). Compared with acetaldehyde alone, NR4A1 agonist increased Smad7 mRNA levels and reduced TGF-β, Smad2/3/4, and ZEB mRNA levels (all P < 0.05). NR4A1 activation suppresses acetaldehyde-induced EMT, as shown by epithelial and mesenchymal marker expression. The inhibition of the TGF-β–Smad2/3/4–ZEB signaling during HSC activation might be involved.